VISUAL AND MATERIAL DIMENSIONS OF HEALTH, RISK AND THE AGEING BODY IN EVERYDAY LIFE. (11th November 2018) - Martin, W; Pilcher, K
Abstract: Health practices are performed, understood and embodied within the context of the daily lives of people as they grow older. There is however limited research into the ways health, risk and the body are lived and experienced when situated within everyday life. This paper draws on data from the study 'Photographing Everyday Life: Ageing, Lived Experiences, Time and Space' funded by the ESRC, UK. The focus of the project was to explore the significance of the ordinary and day-to-day and focus on the everyday meanings, lived experiences, practical activities, and social contexts in which people in mid to later life live their daily lives. We will show how the participants negotiated and mediated their ageing identities and bodies around everyday objects and technologies within the context of daily routines and bodily practices of health and well-being. The analysis highlighted: (1) the role of objects and technologies associated with food practices and how the participants would draw on wider discourses of health promotion and risk. This includes, for example, the material and visual portrayal of diets as 'healthy'; (2) the embodied performance and visual representations of being 'active' as people grow older which was signified by everyday objects such as shoes, clothes and sports equipment; and (3) the incorporation of objects and technologies into routine health practices of daily life, such as, taking medication and supplements, as well as bodily self-surveillance techniques, for example, in relation to bodily weight and chronic conditions.